The effectiveness of the Business Incubator and Entrepreneurial Education in Interest to Start a Business in Vocational School students majoring in Marketing - Raya Sulistyowati (Studies in Learning and Teaching, 2021)
Many media can be a tool for developing entrepreneurial potential in the school environment. One of them is a direct practice in the entrepreneurship laboratory, namely the Business Incubator. Entrepreneurship learning not only provides a theoretical basis for the concept of entrepreneurship but shapes attitudes, behaviours, and a person's mindset in entrepreneurship. Capital investment to prepare students to start new businesses through the experience, skills and knowledge essential to entrepreneurship. The purpose of this study was to determine the management of the Business Incubator at Vocational High School Muhammadiyah 2 Malang, the effectiveness of the role of the Business Incubator as an entrepreneurial learning unit, Empowerment of the Business Incubator as a means of fostering student interest in opening a business. This research uses descriptive qualitative. This study's primary informants consisted of 1 Waka teacher of the Infrastructure and Facilities curriculum, one headteacher of Marketing Laboratory management, 1 Business Incubator management teacher, one entrepreneurship teacher. The research states that the Business Incubator's Management at SMK Muhammadiyah 2 Malang is called the Business Incubator, there are three parts. Namely the photocopy room, used for student practice activities majoring in Office Administration and Islamic Banking, the second production room, used for practical activities majoring in marketing, the third entrepreneurship room, for students majoring in Marketing. The facilities and infrastructure contained in the Business Incubator at Muhammadiyah 2 Malang Vocational School are still not supported. The role of the Business Incubator as an entrepreneurship learning unit at SMK Muhammadiyah 2 Malang is perfect. It can be seen from the increasing enthusiasm of students in participating in entrepreneurship learning. The Business Incubator students have a place to practice entrepreneurial theory taught by the teacher. Empowerment of the Business Incubator to foster student interest in opening a business in students has been running. Some students can see it; most students have been able to read business opportunities and manage sales finances. Thus it can foster the characteristics of an entrepreneurial spirit in students.